(untitled) (Federal University Gusau Faculty of Education Journal, 2026)
This paper assessed language testing on language development among pupils in Ibadan South-West Local Government Area of Oyo State, Nigeria. This study adopted the survey research design. Simple random sampling technique was used to select five schools from the public primary schools in Ibadan South West Local Government Area of Oyo State. Forty primary school pupils were randomly selected from each school, making a total of 200 pupils. In all, 200 pupils participated in the study. One research instrument was used for data collection: Questionnaire on Impact on the enhancement of language development (r=0.76). The instrument was trial tested on 20 pupils that are not part of the schools selected for the study. Data collected were analysed using frequency counts, percentages, mean and standard deviation. Finding of the study indicated that a weighted mean of 2.74 which is greater than the threshold of 2.50. Based on the finding of this study, it was recommended that pupils should not allow their level of language development to decrease. Government should organise seminars and workshops for teachers on methods, strategies and techniques of using language testing to enhance language development in early childhood stage of education in primary schools.